Promoter Architecture of the Porphyromonas gingivalis Fimbrillin Gene - Xie, Hua (American Society for Microbiology, 1999)
Porphyromonas gingivalis fimbriae can mediate adherence to many of the available substrates in the oral cavity. Expression of P. gingivalis fimbriae is regulated at the transcriptional level by environmental signals, such as temperature and hemin concentration. The arrangement of the upstream promoter and regulatory sequences required for transcription and control of the fimbrial structural gene (fimA) was investigated. Primer extension analysis demonstrated that the transcriptional start site of the fimA gene is located 41 bp upstream from the translational start codon. A region (upf) spanning 648 bp upstream of the start codon to 44 bp downstream of the translational start site was cloned upstream of a promoterless lacZ reporter gene. A series of deletion and base substitution mutations were then generated in the upf region. The constructs were introduced into the chromosome of P. gingivalis, and promoter activity measured by assaying levels of β-galactosidase. The results showed that fimA contains sequences resembling ς(70) promoter consensus sequences, consisting of a −10 region (TATGAC) located at −18 to −23 and a −35 region (TTGTTG) located at −41 to −46 from the transcriptional start point. The AT-rich upstream sequences spanning bases −48 to −85 and bases −90 to −240 were required for full expression of the fimA gene, indicating the existence of positive regulation regions. Moreover, the −48 to −64 region may constitute an UP element, contributing to promoter activity in P. gingivalis. Thus, our data suggest that the P. gingivalis fimA gene has a transcription complex consisting of −10 and −35 sequences, an UP element, and additional AT-rich upstream regulatory sequences.